Effects of Intradialytic Resistance Exercise on Protein Energy Wasting, Physical Performance and Physical Activity in Ambulatory Patients on Dialysis: A Single‐Center Preliminary Study in a Japanese Dialysis Facility. Issue 6 (15th August 2016) - Saitoh, Masakazu; Ogawa, Masumi; Dos Santos, Marcelo Rodrigues; Kondo, Hisae; Suga, Kiichi; Itoh, Haruki; Tabata, Yoichiro
Abstract: Patients under hemodialysis present protein‐energy wasting (PEW), which is related with higher mortality rates. The study aimed to determine whether intradialytic resistance exercise training could improve physical performance, physical activity, and PEW in hemodialysis patients. In single center study, 75 hemodialysis patients were enrolled in an intradialytic resistance exercise training consisting of 20 min of adapted leg press, with a gymnastic ball, 3 days/week, during 9 months on the same day of hemodialysis therapy. Physical performance by short physical performance battery (SPPB), physical activity by life space assessment (LSA), and PEW score based on the nomenclature proposed by the International Society of Renal Nutrition and Metabolism in 2008 were assessed at baseline and after 9 months. Intradialytic resistance exercise training significantly improved SPPB score, LSA score, and PEW score (all, P <  0.05). In addition, intradialytic resistance exercise training improved SPPB score in patients with moderate and severe PEW subgroups ( P <  0.05), associated with reduced prevalence of the patients with moderate to severe PEW (53% vs. 36%, P <  0.05). Intradialytic resistance exercise training was safe and effective to improve physical performance, physical activity, and PEW in hemodialysis patients.